ASPEK HAK CIPTA KARYA KECERDASAN BUATAN DALAM PEMERINTAHAN DI INDONESIA - Muhammad Fahmi Islami (Universitas Labuhanbatu, 2025)
This study examines the copyright aspects of artificial intelligence (AI) works in government in Indonesia, highlighting the legal standing, creator status, and field practices, as well as the regulatory challenges faced. This study uses a normative juridical method with an analysis of relevant laws and case studies of AI practices in government. The research findings indicate that artificial intelligence (AI) works used in government still face legal gaps regarding copyright protection. Furthermore, there is a tension between the principles of public information transparency and intellectual property protection for AI outputs, as well as the potential for copyright infringement on input data used by AI. Therefore, the development of an adaptive and comprehensive legal framework is needed so that copyright protection for artificial intelligence (AI) works in the government sector can be realized fairly and proportionally.Keywords: Copyright, Artificial Intelligence, Works, Government